A three-dimensional model of the human blood-brain barrier to analyse the transport of nanoparticles and astrocyte/endothelial interactions [version 2; referees: 2 approved] - Peddagangannagari Sreekanthreddy; Radka Gromnicova; Heather Davies; James Phillips; Ignacio A. Romero; David Male (F1000Research, 2016)
The aim of this study was to develop a three-dimensional (3D) model of the human blood-brain barrier in vitro, which mimics the cellular architecture of the CNS and could be used to analyse the delivery of nanoparticles to cells of the CNS. The model includes human astrocytes set in a collagen gel, which is overlaid by a monolayer of human brain endothelium (hCMEC/D3 cell line). The model was characterised by transmission electron microscopy (TEM), immunofluorescence microscopy and flow cytometry. A collagenase digestion method could recover the two cell types separately at 92-96% purity.  Astrocytes grown in the gel matrix do not divide and they have reduced expression of aquaporin-4 and the endothelin receptor, type B compared to two-dimensional cultures, but maintain their expression of glial fibrillary acidic protein. The effects of conditioned media from these astrocytes on the barrier phenotype of the endothelium was compared with media from astrocytes grown conventionally on a two-dimensional (2D) substratum. Both induce the expression of tight junction proteins zonula occludens-1 and claudin-5 in hCMEC/D3 cells, but there was no difference between the induced expression levels by the two media. The model has been used to assess the transport of glucose-coated 4nm gold nanoparticles and for leukocyte migration. TEM was used to trace and quantitate the movement of the nanoparticles across the endothelium and into the astrocytes. This blood-brain barrier model is very suitable for assessing delivery of nanoparticles and larger biomolecules to cells of the CNS, following transport across the endothelium.